Adhesion of Salmonella typhimurium to porcine intestinal epithelial surfaces: identification and characterization of two phenotypes. - Isaacson, R E (1992)
Salmonella typhimurium 798 is known to persistently colonize swine. A key step required to initiate colonization of intestines is adhesion of the organism to the intestinal epithelium. However, S. typhimurium 798 initially failed to attach to porcine enterocytes in vitro. An enrichment procedure was used to select adhesive S. typhimurium, and when cells of one colony type were grown in tryptone phosphate broth they were adhesive. Cells from a colony with a different morphology were not adhesive. Adhesion was time dependent, with maximal adhesion occurring at 1 h. As determined by electron microscopy, cells of the adhesive phenotype had pili while none of the cells with the nonadhesive phenotype produced pili. The pili on the adhesive cells were morphologically similar to type 1 pili. Mannose (0.5%) did not affect adhesion, suggesting that the adhesin on strain 798 did not recognize mannose as a receptor. An analysis of envelope proteins from cells of both phenotypes showed that the adhesive-phenotype cells expressed at least 10 unique proteins ranging in size from 20 to 60 kDa. Absorbed antiserum against cells of the adhesive phenotype agglutinated adhesive cells and was used to detect unique surface antigens on the cells of the adhesive phenotype by Western blots (immunoblots). These antigens were in the range of 30 kDa in size. An envelope extract competitively inhibited the binding of S. typhimurium to enterocytes, as did Fab fragments prepared from the absorbed serum. Cells of both phenotypes contained two plasmids, and each had identical restriction digestion patterns. Cells of the adhesive phenotype consistently were found to be more readily phagocytosed by pig leukocytes, and once in the phagocytes they survived better than cells of the nonadhesive phenotype.